Evaluation of Topical Gels Containing Ketorolac Tromethamine on Inflammation and Hyperalgesia in Rats - Pabreja, Kavita; Dua, Kamal; Gorajana, Adinarayana (Anti-Inflammatory & Anti-Allergy Agents in Medicinal Chemistry, 2011)
Over recent years, non-steroidal anti-inflammatory drugs (NSAIDs) have been increasingly introduced as topical preparations as they are simple to apply and deliver high drug concentrations locally with limited side effects. Ketorolac trometamol (KT), a potent COX-2 inhibitor, produces typical side effects of NSAIDs when given orally and systemically. Hence the present investigation encompasses the development of topical formulations employing different dermatological bases and evaluated for its efficacy and safety. Standard procedures were followed to test the antiinflammatory and antihyperalgesic effects in male Wistar albino rats. Amongst the various semisolid formulations, the formulation containing hydroalcoholic carbopol gel base (KT1) was found to be significantly (p < 0.05) more effective in inhibiting hyperalgesia associated with inflammation (79.69±1.51 after 5 h of carrageenan administration) as compared to formulation containing plain carbopol gel base (68.75±2.76) and PEG base 73.44±1.23. This demonstrates the suitability of carbopol gel base as an ideal dermatological base for ketorolac trometamol topical formulation and thus providing an ample credence for better therapeutic efficacy.
Keywords: NSAID